The Influence of Work Motivation and Work Environment on the Performance of TNI Pusjarah personnel - Yuliana, Eva (Dinasti Publisher, 2025)
This study aims to analyze the effect of work motivation and work environment on personnel performance at the TNI History Center (Pusjarah). The research uses a quantitative approach with a survey method. The population in this study consisted of 120 personnel, and a sample of 40 respondents was selected using a simple random sampling technique. Data collection was carried out through questionnaires and analyzed using multiple linear regression. The results show that work motivation and work environment have a significant positive effect on personnel performance, both partially and simultaneously. The regression equation obtained is Y = 1.215 + 0.456.X1 + 0.389.X2 + e, where work motivation (X1) and work environment (X2) significantly contribute to the improvement of personnel performance (Y). The coefficient of determination (R²) of 0.756 indicates that 75.6% of the variance in personnel performance can be explained by these two variables, while the remaining 24.4% is influenced by other factors outside the model. This study concludes that increasing personnel motivation and creating a supportive work environment are essential for enhancing personnel performance. Further research is recommended to explore other variables affecting performance.